Do Visits and Discourses Enhance Students’ Learning Skills? Adakah Lawatan Dan Wacana Meningkatkan Kemahiran Pembelajaran Pelajar? - Anuar, Nureen Khairina; Mod Asri, Norain; Abdullah AL-Hadi, Azrina (Journal of Human Capital Development (JHCD), 2025)
Teaching and learning (T&L) methods should be diversified, including through the implementation of visit and discourse activities. Thus, the objective of this study is to analyse students’ perceptions of the impact of visits and discourse on them. Therefore, questionnaires were distributed to students majoring in economics, business administration, accounting and entrepreneurship - fields that heavily rely on industry networking. Through the factor analysis conducted, four main findings were obtained. Firstly, students are more inclined to select courses or subjects that combine several teaching methods, including visits, discourses and lectures. Secondly, visits and discourses can improve students’ understanding, motivation and academic performance. Thirdly, visits and discourse help students become more proficient communicators, particularly with people outside of the university. Fourthly, students’ leadership levels are also improved through participation in visits and discourses with the industry. Therefore, the organisation of visits and discourses in courses taken by students needs to be encouraged and intensified to increase the employability of graduates.